Marketing Communication Strategy To Improve Tourism Potential - M. Ali Syamsuddin Amin; Peri Priansah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
One of the main cultural attractions and the main attraction of tourism in the Kuningan regency is Curug Putri Palutungan. The tourism potential of the Kuningan regency was also supported by good access and transportation facilities. To reach the tourist attraction area that once was separated by many rivers, several bridges were built to facilitate tourists the tourist attraction. The tourist potential of the Curug Putri Palutungan is a mixture of the natural charm of mountainous forests and clear waterfalls, backed by a fresh mountain air that challenges you to explore the nature of the mystery of the forest. In this article, the authors use a qualitative method when conducting descriptive studies on the object of writing, because this method is an appropriate method to search for social fields and in particular communication. Qualitative writing methods that will be used to better understand the phenomena related to psychological aspects, behavior, attitudes, responses, opinions, feelings, desires and desires of a person or group. The marketing communication strategy of the Office of Youth, Sports, and Tourism to increase the tourism potential of the regency of Curug Putri Palutungan is one of them through advertising, that is, the installation of banners/billboards, print media advertising, online media advertising, Kuningan FM radio ads.